Comparison of two-dimensional strain analysis using vendor-independent and vendor-specific software in adult and pediatric patients - Anwar, Shafkat (JRSM Cardiovasc Dis, 2017)
INTRODUCTION: Two-dimensional strain analysis is a powerful analysis modality, however, clinical utilization has been limited by variability between different analysis systems and operators. We compared strain in adults and children using vendor-specific and vendor-independent software to evaluate variability. METHODS: One hundred and ten subjects (50/110 pediatric, 80/110 normal left ventricular function) had echocardiograms with a General Electric ultrasound scanner between September 2010 and January 2012. Left ventricular longitudinal strain was derived with EchoPAC (General Electric, v10.8.1), a vendor-specific software, and Velocity Vector Imaging (Siemens, v3.5), which is vendor-independent. Three independent readers analyzed all the echocardiograms yielding 330 datasets. RESULTS: Mean left ventricular global longitudinal Lagrangian strain was −18.1 ± SD 4.4% for EchoPAC and −15.3 ± SD 4.1% for Velocity Vector Imaging. Velocity Vector Imaging yielded lower absolute global longitudinal Lagrangian strain by mean 2.9 (±SD 2.7, p < 0.0001), and lower regional longitudinal strain. These differences persisted in normal subjects versus those with cardiomyopathy. Longitudinal strain differences were slightly higher in the pediatric cohort. There was no significant difference in inter-observer longitudinal strain and a small difference in intra-observer strain between analysis systems. On repeat measurements, a significant change in global longitudinal Lagrangian strain occurred after the difference exceeded 3–5 strain points for EchoPAC and Velocity Vector Imaging, respectively. CONCLUSION: Velocity Vector Imaging produces lower left ventricular longitudinal strain values versus EchoPAC for the same echo images. Both systems have similar inter-observer variability, Velocity Vector Imaging slightly higher intra-observer variability. A statistically significant change in global longitudinal Lagrangian strain occurs with changes >3–5 strain points on repeat measurements. Strain values between the systems are not interchangeable.